A comparative study on tricuspid valve repair using De Vega’s annuloplasty technique and modified De Vega’s technique using polytetrafluoroethylene band - Palanisamy, Anbukumar; Bose, Karthikeyan; Rani, P.; Vijayan, T. Muthu; Baylis, Marwin Manoa (International Surgery Journal, 2022)
Background: The aim of the study was to compare the outcomes of tricuspid valve repair (TVR) with repair techniques for functional tricuspid regurgitation (TR), DeVega’s technique and modified DeVega’s technique using Polytetrafluoroethylene band. Methods: A total of 37 patients who underwent TVR at Madurai Medical College from September 2019 to November 2021 formed into Group A, consisting of 16 patients who had DeVega’s procedure done and Group B, consisting of 21 patients who had modified DeVega’s procedure using Polytetrafluoroethylene band. In addition, in 80% of patients with rheumatic heart disease (RHD), concurrent surgeries included mitral valve replacement (MVR) and double valve replacement (DVR) in 20% of patients. Clinical and echocardiographic follow-up data were also collected for analysis. Results: All 37 patients were examined and followed up after 3 months and 6 months. Group A De Vegas- 9 out of 16 patients (56%) had mild TR,4 out of 16 (25%) patients had moderate TR, and 3 out of 16 (19%) patients had severe TR. Group B Modified De Vegas- 16 out of 21 patients (76%) had mild TR, 4 out of 21 (19%) patients had moderate TR, and 2 out of 21 (5%) had severe TR. Conclusions: Tricuspid valve annuloplasty utilizing a modified De Vega’s procedure with a polytetrafluoroethylene band was shown to be beneficial when patients were followed for three and six months, respectively.